PENGEMBANGAN MICRO MODUL PADA MATA KULIAH PENGEMBANGAN MEDIA VIDEO UNTUK MAHASISWA PRODI TEKNOLOGI PENDIDIKAN - Aril Febrianto; Abd Haling; Abdul Hakim (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The availability of learning materials that support independent learning is an important factor in improving the quality of higher education. In the Video Media Development course, students often experience difficulties in understanding the stages of video media development systematically due to the limited availability of instructional materials that are practical, concise, and well-structured. This study aimed to develop a micro module that is valid and practical as a supplementary learning resource for the Video Media Development course. The study employed a Research and Development (R&D) approach using the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. The research subjects included material experts, media experts, instructional experts, and students of the Educational Technology Study Program at Universitas Negeri Makassar. Data were collected through interviews, needs assessment questionnaires, expert validation questionnaires, and student response questionnaires. The findings revealed that the level of student need for the developed micro module reached 94%, indicating a highly needed category. The validation results showed that the material expert assessment reached 88%, the media expert assessment reached 100%, and the instructional expert assessment reached 92%, all of which were categorized as highly valid. Furthermore, the practicality test involving 43 students obtained a score of 89.22%, indicating a highly practical category. These findings demonstrate that the developed micro module is feasible for use as a supplementary learning resource in the Video Media Development course and has the potential to support students’ independent learning effectively.